2012
DOI: 10.1007/s00216-012-6345-4
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism detection by optical DNA-based sensing coupled with whole genomic amplification

Abstract: The work presented here deals with the optimization of a strategy for detection of single nucleotide polymorphisms based on surface plasmon resonance imaging. First, a sandwich-like assay was designed, and oligonucleotide sequences were computationally selected in order to study optimized conditions for the detection of the rs1045642 single nucleotide polymorphism in the gene ABCB1. Then the strategy was optimized on a surface plasmon resonance imaging biosensor using synthetic DNA sequences in order to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…SNP discrimination was performed in genomic DNA extracted from human lymphocytes and randomly enriched at 6 mg/L (∼2.8 fM) by whole genome amplification (WGA). The measures were reproducible (CV% <9 %) and the sensor was reusable for up to 20 times [96].…”
Section: Point Mutation Detectionmentioning
confidence: 93%
See 1 more Smart Citation
“…SNP discrimination was performed in genomic DNA extracted from human lymphocytes and randomly enriched at 6 mg/L (∼2.8 fM) by whole genome amplification (WGA). The measures were reproducible (CV% <9 %) and the sensor was reusable for up to 20 times [96].…”
Section: Point Mutation Detectionmentioning
confidence: 93%
“…In particular, SPR was used as a tool for the detection of point mutation related to tumor suppressor genes (e.g., TP53 [90][91][92][93] and K-Ras [94]), cancer disease [95,96], and hereditary disease [97][98][99][100][101][102].…”
Section: Point Mutation Detectionmentioning
confidence: 99%
“…The assay design, a dual-targeting format (Fig. 1), involves a thiolated probe (hybridizing probe, HProbe, red sequence) immobilized on the chip to hybridize the fragmented DNA on a specific portion of the multidrug resistance (MDR1) gene and on three discriminating probes (single nucleotide polymorphisms C/T/A, SnpProbesC/T/A, dark gray sequence) to genotype the C3435T polymorphic site (yellow cross along the genomic DNA fragment, blue sequence) through their full matching or one-base mismatching discrimination of the specific base present in the tested allele genotype [16]. A thiolated negative control probe (NProbe, green sequence) was designed on the enhanced green fluorescence protein (EGFP) gene, not present in the human MDR1 gene, and was used to monitor the selectivity of the hybridization of HProbe toward the human genomic target.…”
Section: Detection and Genotyping Strategymentioning
confidence: 99%
“…Alternatively, we investigated the sensitive and selective label-free detection of human genomic DNA sequences by fine-tuning of the multiple steps involved in the bioassay, from the selection criteria of DNA probes to the sample pretreatment [15]. We also demonstrated that the presence of SNP could be discriminated in matrices randomly amplified by whole genome amplification (WGA) [16] thanks to the tuning of the DNA probe features (length and functionalization). These recent researches represented the starting point for the ultimate and most challenging application of the method, i.e., the allele discrimination of the gene directly in the unamplified DNA samples extracted from human blood (lymphocytes), bypassing sample enrichment steps (e.g., PCR or WGA) which are time-and reagentconsuming [12].…”
Section: Introductionmentioning
confidence: 99%
“…In nucleic acid sensing, the single-stranded DNA/ RNA probes are often employed as the sensor probes, since by virtue of their capacity of binding to their complementary target nucleic acid strands with high sequence-specificity, they can almost always detect the presence of the specific target strands in the sample analyte solution, without error. Regarding transduction of the molecular recognition event into an electronic signal, mostly the optical, electrochemical, electrical, mechanical, acoustic or thermal methods are applied in the current nucleic acid sensors [2][3][4][5][6].…”
mentioning
confidence: 99%